Model Penataan Permukiman Kumuh Untuk Pengelolaan Bencana di Kawasan Pesisir Makassar - Naidah Naing; Muhammad Ikhsan Andi (Universitas Muslim Indonesia, 2016)
After finding a model of a characteristic mapping system based on local wisdom for disaster management in coastal areas in Year I, the next year's research will be directed to advanced applied research. This research aims to research disaster adaptation technology to settlements and infrastructure in coastal areas based on basic problems and existing local wisdom. Technological research concerns technologies used in anticipating settlements from coastal abrasion, strong winds and other climate changes. In addition, the structure of the residential environment in disaster management, housing structure and construction and residential infrastructure will also be studied. The results of this second phase of research are in the form of a technology system that can be applied directly to the area around settlements and housing in managing disasters on the coast of Makassar. The method used in this 2nd year research is descriptive-evaluative using two approaches, namely the Morphological Approach and Behaviour Approach and Architectural Appproach. Data analysis in this study was carried out using spatial analysis techniques and descriptive analysis. The result of the 2nd year of research is a technological design of residential areas for disaster mitigation. Which includes (1) Structural technology design of residential areas consisting of; a) wave barrier b) prevention of coastal abrasion c) coastal vegetation d) infrastructure facilities e) facilities and infrastructure; (2) House construction design for disaster mitigation, consisting of: a) lower structure b) house body structure c) roof structure d) house material e) frame structure f) and house parts (floor, roof wall/ceiling).